Chronic Medical Conditions and Negative Affect; Racial Variation in Reciprocal Associations Over Time - Assari, Shervin; Lankarani, Maryam Moghani (Frontiers in Psychiatry, 2016)
Background: Black-White health paradox can be defined as a lower frequency of depression despite a higher prevalence of economic and social adversities as well as chronic medical conditions (CMC) among American Blacks compared to American Whites. Based on this paradox, the CMC - depressive symptoms link is expected to be weaker among Blacks and Whites. We conducted a 10 year longitudinal study to compare Blacks and Whites for bidirectional associations between number of CMC and negative affect. Methods: We used data from the MIDUS (Midlife in the United States), a nationally representative longitudinal study of American adults. A total number of 7,108 individuals with age range 25 to 75 (N = 7,108) were followed for 10 years from 1995 to 2004. Age, gender, and socioeconomic status (education and income) measured at baseline were controls. Negative affect and chronic medical conditions were measured at baseline and end of follow up. Race was the moderator. Linear regression analysis was used to test the moderating effect of race on the reciprocal associations between CMC and negative affect, net of covariates. Results: In the pooled sample, while baseline CMC was predictive of an increase in negative affect over time, baseline negative affect was also predictive of an increase in CMC. We found interactions between race and baseline CMC on change in depressive symptoms, as well as race with negative affect on CMC change. Conclusion: Blacks and Whites differ in reciprocal links between CMC and negative affect over time. This finding replicates recent studies on differential links between psychosocial outcomes and physical health based on race. Findings may help us better understand how Black - White health paradox develops across mid and later life.